Genomics and Public Health Research: Can the State Allow Access to Genomic Databases? - J Cousineau; N Girard; C Monardes; T Leroux; M Stanton Jean (Tehran University of Medical Sciences, 2012)
Because many diseases are multifactorial disorders, the scientific progress in genomics and genetics should be taken into consideration in public health research. In this context, genomic databases will constitute an important source of information. Consequently, it is important to identify and characterize the State's role and authority on matters related to public health, in order to verify whether it has access to such databases while engaging in public health genomic research. We first consider the evolution of the concept of public health, as well as its core functions, using a comparative approach (e.g. WHO, PAHO, CDC and the Canadian province of Quebec). Following an analysis of relevant Quebec legislation, the precautionary principle is examined as a possible avenue to justify State access to and use of genomic databases for research purposes. Finally, we consider the Influenza pandemic plans developed by WHO, Canada, and Quebec, as examples of key tools framing public health decision-making process. We observed that State powers in public health, are not, in Quebec, well adapted to the expansion of genomics research. We propose that the scope of the concept of research in public health should be clear and include the following characteristics: a commitment to the health and well-being of the population and to their determinants; the inclusion of both applied research and basic research; and, an appropriate model of governance (authorization, follow-up, consent, etc.). We also suggest that the strategic approach version of the precautionary principle could guide collective choices in these matters.